2000
DOI: 10.2337/diabetes.49.12.2196
|View full text |Cite
|
Sign up to set email alerts
|

A common promoter variant of the leptin gene is associated with changes in the relationship between serum leptin and fat mass in obese girls.

Abstract: Mutations in the leptin gene lead to rare obese syndromes of Mendelian inheritance in humans and rodents. However, no relevant mutations are found in the coding region of leptin gene DNA in patients with common multifactorial obesity. These obese patients tend to have an elevation of serum leptin proportional to their adiposity but with a rather wide dispersion of leptin levels for a given body fat content, which in part is attributable to sexual dimorphism. The current study, performed in two independent Cauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
101
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(126 citation statements)
references
References 34 publications
22
101
0
3
Order By: Relevance
“…Using LEP 19GG as the referent group, the recalculated FL risk estimate for the LEP 19AA genotype is 0.6 (95% CI 0.3 -1.3), similar to the OR of 0.5 (95% CI 0.3 -0.8) presented here. As has been observed elsewhere, the BMIs of our controls were not correlated with LEP 19G4A (r ¼ 0.014, P ¼ 0.70) (Karvonen et al, 1998;Lucantoni et al, 2000), LEP À2548G4A (r ¼ À0.013, P ¼ 0.72) (Mammes et al, 1998;Le Stunff et al, 2000), LEPR 223Q4R (r ¼ À0.008, P ¼ 0.83) (Gotoda et al, 1997;Rosmond et al, 2000;Wauters et al, 2001) or APM1 276G4T (r ¼ À0.024, P ¼ 0.51) (Menzaghi et al, 2002;Fumeron et al, 2004). Moreover, this and the previous report by Skibola et al found little evidence that risks associated with BMI varied by genotype.…”
Section: Discussionsupporting
confidence: 71%
“…Using LEP 19GG as the referent group, the recalculated FL risk estimate for the LEP 19AA genotype is 0.6 (95% CI 0.3 -1.3), similar to the OR of 0.5 (95% CI 0.3 -0.8) presented here. As has been observed elsewhere, the BMIs of our controls were not correlated with LEP 19G4A (r ¼ 0.014, P ¼ 0.70) (Karvonen et al, 1998;Lucantoni et al, 2000), LEP À2548G4A (r ¼ À0.013, P ¼ 0.72) (Mammes et al, 1998;Le Stunff et al, 2000), LEPR 223Q4R (r ¼ À0.008, P ¼ 0.83) (Gotoda et al, 1997;Rosmond et al, 2000;Wauters et al, 2001) or APM1 276G4T (r ¼ À0.024, P ¼ 0.51) (Menzaghi et al, 2002;Fumeron et al, 2004). Moreover, this and the previous report by Skibola et al found little evidence that risks associated with BMI varied by genotype.…”
Section: Discussionsupporting
confidence: 71%
“…and LEPR polymorphism Q223R (17,27). Higher leptin levels in the CPP group might also associate with SNPs in the LEP promoter (G-2548A) and/or the LEPR genes.…”
Section: Discussionmentioning
confidence: 99%
“…An SNP (G>A variant) in the promoter region of the leptin gene at nt-2548 is associated with higher leptin levels in obese girls (17) and extreme obesity in overweight Europeans and Taiwanese aborigines (18). On the basis of these associations, we hypothesized that the frequency of the G>A variant in the leptin promoter at nt-2548 (rs7799039) or the SNPs in the leptin receptor Q223R (rs1137101) or K109R (rs1137100) may be more frequent in girls with CPP.…”
mentioning
confidence: 99%
“…Adolescents with recent and severe obesity suit this purpose. Their metabolic features have been characterized (48,59,60). According to epidemiology, their risk of future IGT and type 2 ODDM is important (61).…”
Section: Measuring Pathogenic Traits Before Disease Startsmentioning
confidence: 99%
“…Trying to relate candidate genes bearing common variants to proximal phenotypes is an attempt to make sense of what is going on between the top and the bottom. We used this approach for association studies between insulin levels and insulin gene polymorphisms (47), leptin levels and leptin gene (48), insulin sensitivity, and IRS1 and IRS2 polymorphisms (49). The research work then proceeds by involving genes in low-level phenotypes (50), then attempts to relate the phenotypes studied with higher-level phenotypes.…”
Section: Studying Low-level Physiological Traitsmentioning
confidence: 99%